Demographic, mental health, and offending characteristics of online child exploitation material offenders: A comparison with contact‐only and dual sexual offenders. (16th April 2018) - Henshaw, Marie; Ogloff, James R. P.; Clough, Jonathan A.
Abstract: Technological advances have dramatically increased the ability to access, distribute and produce child exploitation material (CEM) online, resulting in increased numbers of individuals being charged with CEM offences. This study examined the demographic, mental health, and offending characteristics of CEM offenders ( n = 456) in comparison to child contact sexual offenders ( n = 493) and offenders with a history of both CEM and contact offences (dual offenders, n = 256). A robust data linkage methodology was employed to link records from statewide corrections services with policing and mental health records in Victoria, Australia. The results indicated that CEM offenders differed from both contact and dual offenders, and that the groups were primarily differentiated based on two factors: antisocial orientation and sexual deviance. CEM offenders demonstrated high rates of sexual deviance but low rates of antisociality, contact offenders exhibited the opposite pattern, and dual offenders had both high sexual deviance and antisociality. The findings suggest that existing sexual offender assessment and treatment frameworks are unlikely to be suitable for exclusive CEM offenders. The implications for future research are discussed.